Manufacture and electrical characterisation of high voltage insulation for superconducting busbars – (Part 2) application techniques and electrical characteristics. (March 2019) - Clayton, N.; Crouchen, M.; Devred, A.; Evans, D.; Gung, C-Y.; Huang, X.; Li, G.; Piccin, R.
Highlights: Details techniques developed to insulate complex-shaped ITER busbars. Insulation formed to fit changes in section around helium pipes. Insulation needs to be void and wrinkle free so far as possible. Insulation must withstand high voltages during ITER machine operation. Insulation manufactured and tested in 3 stages, leading up to full sized busbar. Insulation evaluated by electrical testing, before and after thermal cycles. Abstract: It is planned that the high voltage electrical insulation on the ITER feeder bus bars will consist of interleaved layers of epoxy resin-pre-impregnated glass tapes ('pre-preg') and polyimide. The development and characterisation of these materials was detailed in Part 1 of this report[1] . This paper provides details of the techniques adopted to fully insulate the complex shape of the busbars, forming insulation to fit the many changes in section. Additionally and so far as is reasonably practicable, the insulation should be void and wrinkle free around the helium inlet and outlet pipes that protrude from the surface of the current leads. High voltages will be developed during the pulsed operation of some ITER magnets and in a fault condition, voltages are likely to rise even further. It is therefore necessary to ensure that the insulation can reliably withstand high voltages over the estimated 30, 000 operational cycles of the ITER device. The selected materials were processed and techniques developed via three stages (a) short length but full section of current lead (so called, mini mock-up), (b) longer lengths of full cross-section current lead and joint (mock-up) and (c) full sized, busbar. Trials on (a) and (b) were carried out at Rockwood Composites in the UK, tested at the ITER Organization in France and the full sized busbar insulated and tested at the Institute of Plasma Physics (ASIPP), Hefei, PR China. Insulation effectiveness was assessed by measuring the insulation resistance (IR), and performing partial discharge and Paschen tests, before and after thermal cycles to 77 K. All of the criteria established by the ITER organization were met.